The exploration and diversity of red fruit (Pandanus conoideus L.) from Papua based on its physical characteristics and chemical composition (Biodiversitas Journal of Biological Diversity, 2011)
Murtiningrum, Sarungallo ZL, Mawikere NL. 2012. The exploration and diversity of red fruit (Pandanus conoideus L.) from Papua based on its physical characteristics and chemical composition. Biodiversitas 13: 124-129. The aim of this study was to determine the diversity of red fruit based on its physical characteristics and chemical composition. Exploratory survey method and laboratory research (pure experiment) were used to assess the physical character and chemical composition of crude red fruit. Physical character of each accession showed a variation on fruit color (dark red and red); the fruit and single fruit (drupa) length ranged from 21-71 cm and 1.2-1.8cm, respectively. The dried red fruit contains 2.03- 3.50% ash, 3.12-6.48% protein, 11.21-30.72% fat, 43.86-79.66% carbohydrate, 3.78- 21.88 mg/100g vitamin C, 2.00-3.14 mg/100g vitamin B1, 0.53-1.11% Ca, 8.32-123.03 ppm Fe, and 0.01-0,33% P, with total carotenoids and total tocopherol ranging from 332.65-3309.42 ppm and 964.52-11917.81 ppm. The clustering analysis result of red fruit based on its physical characteristic and chemical composition showed that the related accessions was U Saem and Tawi Magari, having a 25% similarity. The accession U Saem and Tawi Magari had the highest level of similarity in total carotenoids and total tocopherol. Furthermore, they also perform similar physical characteristics by having triangular cylinder shape, red flesh color, and fruit length category.
Keywords: red fruit, Pandanus conoideus, accession, physical, chemical, cluster